Development of Waqf from an Islamic Perspective through the Land Professional Society of Malaysia in an Effort to Increase Waqf Literacy - Abdullah, Putri Allana; Omar, Ismail Bin; Abdullah, Iqbal Alan; Utami, Pertiwi; Zuhriyah, Nur Azizah; Monalysa, Lita; Basrowi; Satriawan, Dedi; Widiawati, Septi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Partners for this International Community Service activity are the Malaysian Land Professional Association (PERTAMA) community and also lecturers from various universities in Malaysia and Indonesia. The partners' problems are: 1) Community waqf literacy still needs to be improved, 2) Community participation in waqf still needs to improve, 3) The use of social media to disseminate information about waqf development still needs to be improved, and 4) Cooperation between institutions related to efforts to increase waqf literacy still needs to be improved. Based on these three problems, the solutions included: 1) Efforts to increase waqf literacy through discussions on waqf development, 2) Carrying out seminars on increasing community participation, especially in this activity, namely community members and lecturers, 3) Promote social media to disseminate waqf information and increase waqf literacy, and 4) Collaborating with PERTAMA to convey the waqf literacy message. A qualitative approach was used for data collection using the discussion group forum method. After the implementation of the activities, several changes occurred as follows: 1) The participants know the importance of developing waqf and the law regarding waqf, 2) The participants know about various training programs for waqf development, 3) Participants can understand how to use multiple social media to support increasing waqf literacy, and 4) Establishing collaboration/partnerships with PERTAMA communities to support the Zakat literacy program. This international community service activity successfully supported efforts to increase waqf literacy for academics from various universities and PERTAMA members in Malaysia.